2017
DOI: 10.1021/acs.bioconjchem.7b00311
|View full text |Cite
|
Sign up to set email alerts
|

p-NO2–Bn–H4neunpa and H4neunpa–Trastuzumab: Bifunctional Chelator for Radiometalpharmaceuticals and 111In Immuno-Single Photon Emission Computed Tomography Imaging

Abstract: Potentially nonadentate (NO) bifunctional chelator p-SCN-Bn-Hneunpa and its immunoconjugate Hneunpa-trastuzumab for In radiolabeling are synthesized. The ability of p-SCN-Bn-Hneunpa and Hneunpa-trastuzumab to quantitatively radiolabel InCl at an ambient temperature within 15 or 30 min, respectively, is presented. Thermodynamic stability determination with In, Bi, and La resulted in high conditional stability constant (pM) values. In vitro human serum stability assays have demonstrated both In complexes to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 38 publications
7
74
0
Order By: Relevance
“…Chelation of 227 Th using the nonadentate ligands 4 and 5 resulted in no or low yields. Although it was reported that 111 In-labeled 4, H 4 neunpa-p-Bn-NO 2 , has exceptional stability, 31 the extended diethylenetriamine backbone and the nonadentate N 5 O 4 coordination motif does not seem to be suitable for coordinating the thorium ion. Attempts at chelation of 227 Th with ligand 5, H 4 pypa, resulted in low labeling yields with multiple radioactive peaks, including one large peak observed from t R = 11 min to t R = 20 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelation of 227 Th using the nonadentate ligands 4 and 5 resulted in no or low yields. Although it was reported that 111 In-labeled 4, H 4 neunpa-p-Bn-NO 2 , has exceptional stability, 31 the extended diethylenetriamine backbone and the nonadentate N 5 O 4 coordination motif does not seem to be suitable for coordinating the thorium ion. Attempts at chelation of 227 Th with ligand 5, H 4 pypa, resulted in low labeling yields with multiple radioactive peaks, including one large peak observed from t R = 11 min to t R = 20 min.…”
Section: Discussionmentioning
confidence: 99%
“…Ligands containing the pa moieties, 3-6, were prepared as previously published. 28,[31][32][33][34][35]…”
Section: General Considerationsmentioning
confidence: 99%
“…The patient was treated with two cycles of 213 Bi-PSMA-617 with a cumulative activity of 592 MBq. Restaging with 68 Ga-PSMA PET/CT after 11 months showed an outstanding molecular imaging response. This patient also exhibited a biochemical response (decrease in prostate-specific antigen levels from 237 µg/L to 43 µg/L) [80].…”
Section: Bi-psmamentioning
confidence: 97%
“…CAFs, in contrast with normal fibroblasts, overexpress fibroblast activation protein α (FAP). Novel radioprobes, both for diagnostic and therapeutic applications, were designed and are based on FAP inhibitors (FAPI) as vector molecule (e.g., 68 Ga-DOTA-FAPI-46). FAPI PET images are characterized by rapid kinetics, very low background activity (no uptake in brain, muscle, brown fat, bowel, etc.)…”
Section: Future Perspectives Of 213 Bi-tatmentioning
confidence: 99%
See 1 more Smart Citation